2005
DOI: 10.1177/1363461505050709
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Paralysis as Spiritual Experience

Abstract: This article presents an overview of the sleep paralysis experience from both a cultural and a historical perspective. The robust, complex phenomenological pattern that represents the subjective experience of sleep paralysis is documented and illustrated. Examples are given showing that, for a majority of subjects, sleep paralysis is taken to be a kind of spiritual experience. This is, in part, because of the very common perception of a non-physical 'threatening presence' that is part of the event. Examples fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 14 publications
2
54
0
12
Order By: Relevance
“…Ilmunud on ka mõned painajakogemuse psühhoanalüütili-sed tõlgendused, milles nähakse nähtuse põhjusena neurootiliselt allasurutud seksuaalsust (nt Jones 1931). Religiooniteadlane David Hufford (1989Hufford ( , 2005 on seisukohal, et üleloomuliku rünnaku jutud põhinevad reaalsetel kogemustel, ent need kogemused võivad edasirääkimise käigus kohaneda olemasoleva jutustamistraditsiooniga.…”
Section: Sissejuhatuseksunclassified
“…Ilmunud on ka mõned painajakogemuse psühhoanalüütili-sed tõlgendused, milles nähakse nähtuse põhjusena neurootiliselt allasurutud seksuaalsust (nt Jones 1931). Religiooniteadlane David Hufford (1989Hufford ( , 2005 on seisukohal, et üleloomuliku rünnaku jutud põhinevad reaalsetel kogemustel, ent need kogemused võivad edasirääkimise käigus kohaneda olemasoleva jutustamistraditsiooniga.…”
Section: Sissejuhatuseksunclassified
“…Aqtuqsinniq (ou uqumangirniq dans le sud Baffin et au Nunavik) désigne la paralysie du sommeil, une parasomnie associée à la phase paradoxale du sommeil, dont des descriptions identiques ont été rapportées de partout dans le monde (Hufford 2005): au moment de son endormissement ou de son réveil, la personne consciente de ce qui se passe autour d'elle est incapable de bouger et de parler à cause de l'absence totale de tonus musculaire typique du sommeil paradoxal. Cette parasomnie, dont la prévalence semble variable selon les sociétés, apparaît fréquente chez les Inuit.…”
Section: La Base Kappia-unclassified
“…harmful or undesired reactions stemming from inert, sham or dummy treatment [78], research on religious and spiritual coping has identified 'anger at God or a deity' as an important predictor for poor mental health and poor coping outcomes [79,80]. It has also been suggested that some spiritual experiences may induce severe distress [81,82], states of crisis [83], and/or abjectly negative physiological effects, and in this regard, literature addressing Voodoo rituals is particularly illustrative of the relative power of nocebo (for review, see [84,85]). …”
Section: Investigating the Relationship Between Spirituality And Healthmentioning
confidence: 99%